Antihyperglycemic Activity Test of Ethanol Extract of Mulberry Leaves (Morus alba L.) Against Zebrafish (Danio rerio) - Burhan, Asril (Politeknik Kesehatan Makassar, 2022)
Hyperglycemia is a state of high blood sugar with a value more than normal because the body does not produce insulin or insulin does not work properly. One of the plants that has the potential toas an antihyperglycemicactagent is mulberry (Morus alba L.) because the flavanoid content causes a reduction in glucose and fructose absorption from the intestine so that blood glucose levels fall. This study aims to determine the activity and dosage of ethanol extract of mulberry leaves that have the best effect on reducing blood glucose levels in zebrafish. This study used zebrafish (Danio rerio) induced by alloxan and glucose to raise blood glucose levels. The test animals used were 60 animals divided into 6 groups, namely group 1 positive control (Aloxan 0.1+ glucose 1% and Metformin 100 µM), group 2 negative control (Aloxan 0.1% + glucose 1%), group 3 without treatment, group 4 extract dose 200 mg / 2L, group 5 extract dose 300 mg / 2L, group 6 extract dose 400 mg / 2L. Then measured glucose levels using a glucometer (Autocheck®). The data analysis was performed by the Kruskal-Wallis test. The results showed that a dose of 400 mg / 2L had the ability to reduce blood glucose levels similar to that without treatment.